Regional Anaesthesia in a Combat Setting - Bala Chandran NAMBIAR; Bhavna PAHWA; Moumita GHATAK (Modern Medicine)
Background: Recent advances in combat casualty care have contributed significantly to higher survival rates in previously fatal injuries from military trauma. However, most of the literature comes from international data during Operation Enduring Freedom and Operation Iraqi Freedom. Despite having conflicts, counter insurgency operations spanning over decades, very few studies in Indian scenario have analyzed injuries related to Combat and Military Trauma. Method: A retrospective observational study was done based on the records of management of military trauma cases in a zonal hospital deployed in an operational area. All trauma/ combat casualties over a one year period from Oct 2018 to Oct 2019 were included and data was segregated based on type of mechanism of trauma, limb injuries involved, and choice of anaesthesia given based on type of surgery. Results: Total 371 combat casualties were included in the study, maximum patients had splinter injuries with grenade blast (43.4%), followed by gunshot wounds (39.9%). Other injuries included mine blast (11.3%) and miscellaneous including road traffic accidents (5.4%). Due to predominant involvement of limbs, regional anaesthesia was used most commonly (78%) and general anaesthesia was used only in 23.7% of cases. Conclusion: In our study maximum casualties were peripheral limb injuries both upper and lower limbs. Regional anaesthesia, peripheral nerve blocks for upper limb injuries and sub arachnoid block for lower limb injuries, were more commonly used in comparison to general anaesthesia (GA), while injuries involving body regions other than limbs were performed exclusively under GA.